Observations of nanocrystalline cubic boron nitride formed with plasma spraying. (1st September 2016) - Madhav Reddy, K.; Hwang, Chawon; Ornek, Metin; Miller, Steven L.; Mayo, William E.; Burgess, Alan; Haber, Richard A.; Hemker, Kevin J.
Abstract: Cubic boron nitride (c-BN) has superior hardness and strength as compared to other ceramics that are commonly used as abrasives and in cutting tool applications. Cubic BN powders are generally produced under high pressures, usually greater than 10 GPa. Here, we report on the synthesis of nanocrystalline c-BN from metastable precursors without high external pressures using a novel plasma spray processing technique. Transmission electron microscopy (TEM) and electron energy loss spectroscopy (EELS) measurements indicate that the initial metastable precursor particles are amorphous and comprised of boron, carbon, nitrogen and oxygen with weak interatomic bonding that may easily undergo phase transformations during plasma spraying. Postmortem X-ray diffraction and TEM analysis of plasma spray deposits reveal the formation of crystalline phases of BN, and high-resolution TEM observations demonstrate that c-BN can be induced during the plasma spray process with the addition of appropriate catalysts. These observations point to a novel pathway for facilitating the transition from a low-density amorphous state to the high-density cubic BN phase. Graphical abstract: Experimental TEM image and calculated image shown for the nanocrystalline cubic boron nitride.